Sistem Akuntansi Penjualan Kredit Pada Toko Bangunan Mt Jaya - Firmani, Maulidi; Ulfa Solihannlisa, Lulu (EKOBIMA, 2025)
This study aims to know the credit sales accounting system at MT Jaya building store. MT Jaya Building Store is a company engaged in the retail sales of building materials established since 2008. The goods traded at MT Jaya Building Store include various building materials and tools for home construction projects. The research method used is a qualitative descriptive method, namely the author conducted research, described the results of observations and analyzed the data obtained in the field. After analyzing and discussing the problem, the author concluded that the credit sales accounting system at the MT Jaya building store is still not good, because the accounting system used is still very simple, records and supporting documents in the credit sales accounting system are still incomplete, and there are still employees who perform dual functions.